Structure and stabilization of the Hendra virus F glycoprotein in its prefusion form - Wong, Joyce J W; Paterson, Reay G; Lamb, Robert A; Jardetzky, Theodore S (Proceedings of the National Academy of Sciences - PNAS, 2016)
Hendra virus (HeV) is one of the two prototypical members of the Henipavirus genus of paramyxoviruses, which are designated biosafety level 4 (BSL-4) organisms due to the high mortality rate of Nipah virus (NiV) and HeV in humans. Paramyxovirus cell entry is mediated by the fusion protein, F, in response to binding of a host receptor by the attachment protein. During posttranslational processing, the fusion peptide of F is released and, upon receptor-induced triggering, inserts into the host cell membrane. As F undergoes a dramatic refolding from its prefusion to postfusion conformation, the fusion peptide brings the host and viral membranes together, allowing entry of the viral RNA. Here, we present the crystal structure of the prefusion form of the HeV F ectodomain. The structure shows very high similarity to the structure of prefusion parainfluenza virus 5 (PIV5) F, with the main structural differences in the membrane distal apical loops and the fusion peptide cleavage loop. Functional assays of mutants show that the apical loop can tolerate perturbation in length and surface residues without loss of function, except for residues involved in the stability and conservation of the F protein fold. Structure-based disulfide mutants were designed to anchor the fusion peptide to conformationally invariant residues of the F head. Two mutants were identified that inhibit F-mediated fusion by stabilizing F in its prefusion conformation.